Regulation of Duopoly: Managed Competition vs. Regulated Monopolies - Asher Wolinsky (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1994)
This paper discusses the regulation of oligopolistic differentiated product industries. The regulator can control the prices, and impose quantity restrictions, but cannot control effectively the quality choices of the firms. We inquire about the optimal choice of regulatory regime–whether and under what conditions managed competition or segmentation of the market between regulated monopolies achieves better results. In the spatial duopoly model analyzed here, unhindered competition will generally result in an inefficient allocation. When the regulator knows the technologies, optimal managed competition results in distortions of the quality choice, but an optimal regulated monopolies regime acheives the first best outcome. When the regulator is uncertain about the technologies neither of these methods will yield the first best outcome. The regulated monopolies regime still tends to produce better quality choices, but managed competition tends to be more effective at extracting rents from the firms. The overall comparison depends on some finer details of the environment.
Keywords: 330